Geographic inequalities in the implementation of the More Doctors Program (Programa Mais Médicos) in a Brazilian state - Moraes, Priscila Lube (2021)
Introduction: The More Doctors Program (Programa Mais Médicos — PMM) arises from the need to enforce the universal right of access to the Brazilian public health system (Sistema Único de Saúde — SUS) and to make health care more equitable in Brazil. Objective: The study analyzed the first cycle (2013–2016) of PMM implementation in 78 municipalities of the state of Espírito Santo. Methods: This is a quantitative study based on secondary data collected from the State Health Secretariat, the National Record of Health Facilities, the Brazilian Institute of Geography and Statistics, and the Jones dos Santos Neves Institute. Municipalities of Espírito Santo were grouped by population size, with the unit of analysis corresponding to the aggregate population and geographic space of each municipality. Data were analyzed using descriptive and inferential statistics. Results: The results of this study showed that the PMM implementation in Espírito Santo contributed to strengthening primary care, increasing the number of physicians and establishing them in both smaller and larger cities. However, they also indicated that vertical geographical inequalities persisted during PMM implementation in municipalities of different population sizes. Conclusions: We emphasize the need for primary care management in the pursuit of an effective and equitable public health system, regardless of population size.